1989
DOI: 10.1002/glia.440020510
|View full text |Cite
|
Sign up to set email alerts
|

In situ demonstration of mature oligodendrocytes and their processes: An immunocytochemical study with a new monoclonal antibody, Rip

Abstract: This paper introduces "Rip" a monoclonal antibody that produces relatively complete staining of oligodendrocytes and their processes in the adult central nervous system (CNS). The distribution of Rip immunoreactivity coincides with that of myelinated axons in both the spinal cord and the cerebellum. In addition, double-immunolabeling experiments demonstrate that Rip stains processes containing myelin basic protein but does not stain processes that express glial fibrillary acidic protein. These results indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
185
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 242 publications
(193 citation statements)
references
References 29 publications
8
185
0
Order By: Relevance
“…Nogo-A is present in all stages of oligodendrocyte differentiation (Huber et al, 2002;Wang et al, 2002b) and is believed to mediate inhibition of neurite outgrowth and axonal regeneration through binding to and activation of neuronal NgR in juxtaposed axons (Wang et al, 2002b;. In the present report, RIP was used to label oligodendrocytes as previously described (Friedman et al, 1989;Nguyen and Pender, 1999;Wennstrom et al, 2004), and we observed an increased number of Nogo-A (+)/RIP (+)cells in ipsilateral white matter following FP brain injury. Although an increased number of glial cells have been observed in the ipsilateral white matter tracts following FP brain injury (Graham et al, 2000), our data are the first to suggest that the number of oligodendrocytes may increase in selected regions following TBI, as previously demonstrated in models of cerebral ischemia (Dewar et al, 2003;Zaidi et al, 2004), spinal cord injury (McTigue et al, 2001) and cortical resection brain injury (Ludwin, 1984).…”
Section: Discussionsupporting
confidence: 73%
“…Nogo-A is present in all stages of oligodendrocyte differentiation (Huber et al, 2002;Wang et al, 2002b) and is believed to mediate inhibition of neurite outgrowth and axonal regeneration through binding to and activation of neuronal NgR in juxtaposed axons (Wang et al, 2002b;. In the present report, RIP was used to label oligodendrocytes as previously described (Friedman et al, 1989;Nguyen and Pender, 1999;Wennstrom et al, 2004), and we observed an increased number of Nogo-A (+)/RIP (+)cells in ipsilateral white matter following FP brain injury. Although an increased number of glial cells have been observed in the ipsilateral white matter tracts following FP brain injury (Graham et al, 2000), our data are the first to suggest that the number of oligodendrocytes may increase in selected regions following TBI, as previously demonstrated in models of cerebral ischemia (Dewar et al, 2003;Zaidi et al, 2004), spinal cord injury (McTigue et al, 2001) and cortical resection brain injury (Ludwin, 1984).…”
Section: Discussionsupporting
confidence: 73%
“…5e,f). Both early-and late-passage neurospheres differentiated after growth factor reduction, as assessed by the presence of RIP þ ive oligodendrocytes 34 , GFAP þ cells with astrocytic morphology 35 , TUJ1 þ ve immature neurons 36,37 and growth hormone releasing hormone (GHRH) þ ive hypothalamic neurons 32 (Fig. 5g).…”
Section: Resultsmentioning
confidence: 99%
“…Oligodendrocytes and myelin were visualized using monoclonal mouse anti-rat Rip antibody (Developmental Studies Hybridoma Bank, University of Iowa, Iowa City, IA) recognizing 2=, 3=-cyclic nucleotide 3=-phosphodiesterase. 32,33 The antibody was biotinylated by Karsten Skjødt, University of Southern Denmark (Odense) and used at a concentration of 0.05 mg/mL. NG2 and CNP stainings were counterstained using toluidine blue to facilitate cell counting.…”
Section: Validation Of Pp Lesionmentioning
confidence: 99%